The Impact of Criminal Policy on Money Laundering Against the Resilience of the Law - Kusbianto Kusbianto; Ariman Sitompul; Adiputra Adiputra; Miftahuddin Miftahuddin (Susbtantive Justice International Journal of Law, 2022)
Differences in the authority of investigators over money laundering crimes committed by members of the Indonesian National Armed Forces lead to disharmony of norms, thus creating polemics in the law enforcement process, especially in efforts to eradicate money laundering. Currently, there is an expansion of investigative competence based on the Decision of the Constitutional Court of the Republic of Indonesia, which states that predicate criminal investigators are officials or bodies authorized by laws and regulations to conduct investigations. Violations committed by members of the Indonesian National Armed Forces against the crime of money laundering should be under the jurisdiction of the Military Court. This study aims to determine the development and impact of legal policies related to members of the Indonesian National Armed Forces who commit criminal acts in the jurisdiction of the Military Court I-03 Padang. The analysis of this research uses a descriptive qualitative approach by using primary and secondary data. The results indicate that the competence of military courts is vulnerable to discontinuing the legal process of money laundering. Military courts should also be given the authority to try Indonesian National Armed Forces members who commit money laundering crimes. Investigation of The Crime of Money Laundering committed by members of the Indonesian National Armed Forces in the ius constituendum must be formulated more firmly in the Money Laundering Law. Thus, the Indonesian National Army members who violate the entered in categorization of General Crimes or non-military will be subject to the general justice system, and in the investigation carried out by investigators in the general court as described in the provisions in accordance with the limitative theory.